Implementation of Construction Management Approach for Improving the Productivity of RMC Plants (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Our has been traditionally labor oriented. The pace of mechanization in the past has been very slow due to the availability of cheap labor in abundance, lack of capital investment and the highly fragmented nature of the construction industry. The degree of mechanization is still around 25%-30% while it is well above 70% in most of the developed countries The liberalization of Indian economy from 1991 onwards paved the way for large scale investments in infrastructure, industrial, housing and agriculture sectors. The new age constructions required speed and superior quality to obtain profitable life cycle cost of the projects. The emerging scenario helped to increase the pace of mechanization and facilitated the establishment of RMC plants on commercial scale to synchronies with the overall development strategy. RMC in India on commercial scale started in 1993 at Pune with only one plant. It has achieved nearly 15% share of the total concrete produced in the country. In some major cities, like Bangalore, Hyderabad, Mumbai and Chennai the share of RMC has reached as high as 50% to 60%. The growth prospects of RMC in India are enormous, provided requisite support is provided by the regulatory authorities, consumers and decision makers during its formative years. In this project the critical factor causing improving productivity will indentify.